Program minda ceria sihat at SMK Mambau / Muhammad Syazwan Maszuan and Muhammad Fikri Jamal - Maszuan, Muhammad Syazwan; Jamal, Muhammad Fikri (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The launch of Program Minda Ceria Sihat at SMK Mambau highlights the vision of nurturing well–rounded individuals. It believes that promoting mental well-being is as crucial as academic excellence. Considering this, we have developed a comprehensive program that aims to support and enhance the mental health of the school community - Program Minda Ceria Sihat. This was a programme organized by batch Suprematrix (Semester 2), bachelor’s degree in Sports Science under the guidance of lecturer Puan Nur Dalilah Dahlan. The main aim of Program Minda Ceria Sihat is to create a safe inclusive environment where individuals can openly address their mental health concerns, seek support, and build a sense of community. Their dedicated team of experienced professionals, including counsellors and educators, are committed to providing guidance and resources tailored to the unique needs of the students, ensuring their mental health remains a top priority. Its belief is that by prioritizing mental health, an environment that fosters personal growth, resilience, and academic success is created. Program Minda Ceria Sihat provides participants with a singular opportunity to investigate the workings of the mind and acquire useful information to improve their intellectual talents. This program offers a thorough and intensive learning experience, covering everything from memory methods to enhancing creative thinking. The program also included motivational talks from renowned experts in the field of intelligence and cognitive development, including one from Puan Norfahana Binti Zulkifli, a Psychology Officer at UiTM Seremban. In this seminar, she shared and explained concepts such as thought exploring and enhancing, problem - solving and other related areas. The Suprematrix students will apply all their skills and knowledge through the games they created.